Analysis and Optimization of a Nonlinear, Continuous, Autoparametric System - Foryś, Anna; Foryś, Andrzej S. (Engineering Transactions, 2002)
In the present paper a transversely vibrating autoparametric system consisting of three non-prismatic rods is presented. The considerations refer especially to stability of the semi-trivial solution. Proper selection of the values of parameters may lead to considerable reduction of the autoparametric resonance effects or may shift the autoparametric resonance to another frequency region.